PEMBERDAYAAN MASYARAKAT PETERNAK BABI DI DESA TOUNELET KECAMATAN SONDER KABUPATEN MINAHASA - MANARISIP, INJILIA; LENGKONG, FLORENCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
Strengthening community potential is a necessity today. Because with a community that has goodpotential, it will be able to manage the resources owned by the Indonesian nation. The purpose of thisresearch is how to empower the community of pig breeders in Tounelet Village, Sonder District, MinahasaRegency. This research design uses qualitative methods, then the data sources in this study use primaryand secondary data and the data collection techniques used are observation, interviews, documentation.The data analysis of this research is data reduction and conclusion drawing. The results showed that theproblem of community empowerment of pig breeders in Tounelet Village was related to economicconditions in terms of buying feed and selling their crops. Therefore, real action is needed to solve theseproblems so that babai breeders can become empowered. Based on the results of the study, it wasconcluded that 1) the extension program to strengthen the potential of the Tounelet Village community aspig breeders did not provide more benefits because the breeders had knowledge and experience inbreeding for generations; 2) The unstable price of animal feed and lack of business capital support facedby breeders as a manifestation of strengthening the potential or power of the pig breeder community hasnot yet been implemented; 3) The unstable selling price of livestock is a manifestation of the lack of accessto protection of the selling price from the government to the pig farming community.Keywords : Community Empowerment, Pig Farmers